PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN RENAISSANCE BALI NUSA DUA RESORT - Made Candra Deivi; Heryanda, Komang Krisna (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This study aims to determine the effect of compensation and work environment on employee performance at Renaissance Bali Nusa Dua Resort. This type of research is casual quantitative research. The population in this study were employees of the Food & Beverage Service department at Renaissance Bali Nusa Dua Resort totaling 58 people. Determination of the sample using the census method. Resort and (3) Compensation and work environment have a significant effect on employee performance at Renaissance Bali Nusa Dua Resort.The instrument used in data collection was a questionnaire. Data processing in this study used the assistance of the SPSS version 25 program. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that: (1) Compensation has a positive and significant effect on employee performance at Renaissance Bali Nusa Dua Resort, (2) The work environment has a positive and significant effect on employee performance at Renaissance Bali Nusa Dua